Reproduction and adaptation - Mascie-Taylor, C. G. N.; Rosetta, Lyliane (Cambridge : Cambridge University Press, 2011)
In the space of one generation major changes have begun to take place in the field of human reproduction. A rapid increase in the control of fertility and the understanding and treatment of sexual health issues have been accompanied by an emerging threat to reproductive function linked to increasing environmental pollution and dramatic changes in lifestyle. Organised around four key themes, this book provides a valuable review of some of the most important recent findings in human reproductive ecology. Major topics include the impact of the environment on reproduction, the role of physical activity and energetics in regulating reproduction, sexual maturation and ovulation assessment and demographic, health and family planning issues. Both theoretical and practical issues are covered, including the evolution and importance of the menopause and the various statistical methods by which researchers can analyse characteristics of the menstrual cycle in field studies.
1. Reproduction and environment / Alan S. McNeilly -- 2. Genetic damage and male reproduction / Michael Joffe -- 3. The microenvironment in health and cancer of the mammary gland / John P. Wiebe -- 4. The energetic cost of physical activity and regulation of reproduction / Darna L. Dufour -- 5. Energetic cost of gestation and lactation in humans / Prakash Shetty -- 6. Adaptive maternal, placental and fetal responses to nutritional extremes in the pregnant adolescent: lessons from sheep / Jacqueline M. Wallace -- 7. Growth and sexual maturation in human and non-human primates: a brief review / Phyllis C. Lee -- 8. The evolution of post-reproductive life: adaptionist scenarios / Lynnette Leidy Sievert -- 9. Analysing the characteristics of the menstrual cycle in field situations in humans: some methodological aspects / Jean-Christophe Thalabard, Laurence Joubin, Lyliane Rosetta and C.G. Nicholas Mascie-Taylor -- 10. An insidious burden of disease: the pathological role of sexually transmitted diseases in fertility / Geoff P. Garnett -- 11. Family planning and unsafe abortion / Anna Glasier -- 12. Global sexual and reproductive health: responding to the needs of adolescents / Molly Secour-Turner, Linda H. Bearinger and Renee Sieving -- 13. Understanding reproductive decisions / Andrew Hinde.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Human reproduction -- Environmental aspects; Fertility, Human -- Environmental aspects; Human ecology